2016
DOI: 10.1093/neuonc/nov321
|View full text |Cite
|
Sign up to set email alerts
|

Core pathway mutations induce de-differentiation of murine astrocytes into glioblastoma stem cells that are sensitive to radiation but resistant to temozolomide

Abstract: A defined set of core signaling pathway mutations induces de-differentiation of cortical murine astrocytes into GSCs with altered chromatin landscapes and transcriptomes. This non-germline genetically engineered mouse model mimics human proneural GBM on histopathological, molecular, and treatment response levels. It may be useful for dissecting the mechanisms of treatment resistance and developing more effective therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 62 publications
4
42
0
Order By: Relevance
“…Moreover, intrinsic properties of the tumor cells within these subtypes may contribute to the observed differences in treatment response. It has been shown that oligodendroglioma cells are more responsive to TMZ than astrocytic glioma cells (Schindelin et al, ; Schmid et al, ). Since our Olig2 staining and histological analysis demonstrated that the PDGFB‐overexpressing model has oligodendroglial features, and our GFAP staining and histological analysis showed that the NF1‐silenced model has astrocytoma features, this point may account for some of the differences in TMZ response seen in our models.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, intrinsic properties of the tumor cells within these subtypes may contribute to the observed differences in treatment response. It has been shown that oligodendroglioma cells are more responsive to TMZ than astrocytic glioma cells (Schindelin et al, ; Schmid et al, ). Since our Olig2 staining and histological analysis demonstrated that the PDGFB‐overexpressing model has oligodendroglial features, and our GFAP staining and histological analysis showed that the NF1‐silenced model has astrocytoma features, this point may account for some of the differences in TMZ response seen in our models.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that TRP mutations induce a primitive, proneural GBM-like gene expression state in cultured murine astrocytes (63). We subsequently found that cultured TRP astrocytes acquire the functional properties of NSC in vitro and cancer stem cells in vivo (51). These results suggest that TRP mutations induce astrocyte dedifferentiation.…”
Section: Trp Mutations Induce Expression Of the Nsc Marker Nestin In mentioning
confidence: 82%
“…We have previously shown that transformation of cultured astrocytes by TRP mutations induces a primitive transcriptome state in vitro (63). We have also found that TRP astrocytes acquire the functional properties of NSC in vitro and cancer stem cells in vivo (51). Here, we show that TRP mutations induce the expression of the primitive maker nestin in situ (Figure 6).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The OTSSP167 and DZNep were utilized as the MELK and EZH2 inhibitors to complement these findings, which have been involved in a great deal of research (39)(40)(41). On the 5th day after intracranial transplantation of dissociated MB25550 CSCs, engraftments were confirmed with microMRI scanning, and mice with equivalent volumes were randomized into three groups for intraperitoneal treatment: OTSSP167 (20 mg/kg), DZNep (20 mg/kg), and control (n ¼ 6/group).…”
Section: Transplantation and Drug Administrationmentioning
confidence: 99%